The World According to Philip K. Dick - Dunst, Alexander; Schlensag, Stefan (Palgrave Macmillan, 2015)
As the first essay collection dedicated to Philip K. Dick in two decades, this volume breaks new ground in science fiction scholarship and brings innovative critical perspectives to the study of one of the twentieth century's most influential authors.
CRIS-Team Scopus Importer:2023-03-09